Model Komunikasi Humas dalam Literasi Media Sosial : (Studi Kasus Direktorat Pendidikan Profesi Guru) - Shintia Ira Claudia; Sa'diyah El Adawiyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The development of technology and social media affects the way we interact and access information. Social media, such as Facebook and Twitter, enable the global exchange of information. The phenomenon of virality accelerates the spread of content, creating new dynamics in delivering messages and influencing public opinion. Digital literacy is the key to dealing with the increasingly advanced technological era, especially through social media. This research aims to observe the communication model of the @ppgkemendikbud Instagram account in providing social literacy about Teacher Professional Education (PPG). This research method is descriptive qualitative with data collection through observation and literature study. The results showed that the Ministry of Education's PPG Instagram account with 1,086 uploads and 462 thousand followers plays a role in providing social literacy about PPG. The success of this account lies in its openness without locking, direct message feature that increases interactivity, and regularly uploading the latest information about PPG, national day commemoration, and education seminars. The PR communication model used involves a two-way approach, covering various PPG highlights, so that it is not only a source of information, but also a place to build a community.